Manajemen Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di MIN 3 Serang - Yan Ansori; Maulana Nur Kholis; Ashari (CV. ITTC INDONESIA, 2025)
The results of the study indicate that the madrasah principal plays a strategic role as a mentor, motivator, manager, supervisor, and evaluator. In implementing these strategies, the madrasah principal applies various strategies such as individual coaching, providing ongoing motivation, implementing work discipline, professional training, and providing awards to high-performing teachers. Supporting factors in improving teacher performance include strong leadership, adequate facilities, ongoing training programs, and a fair and transparent reward system. Inhibiting factors include limited resources, disciplinary challenges, lack of relevant training, and fluctuations in teacher motivation. Theoretically, these findings support and strengthen transformational leadership theory, motivation theory, human resource management theory, and teacher professional development theory. The practical implications of this study indicate the need for an integrated strategy in teacher development through training, rewards, discipline management, and effective communication. This research contributes to improving the quality of education and developing managerial policies in the madrasah environment.